Circ_0085495 knockdown reduces adriamycin resistance in breast cancer through miR-873-5p/integrin β1 axis. Issue 1 (January 2022) - Xie, Hua; Zheng, Rongsheng
Abstract : Circular RNAs (circRNAs) are reported to be related to cancer chemoresistance. However, the role of circ_0085495 in adriamycin (ADM) and its action mechanism has not been elucidated in breast cancer. Cell counting kit-8 was employed to detect cell viability. Quantitative real-time-PCR and western blot were performed to examine the gene and protein expression level. Flow cytometry and colony formation assay were conducted to measure cell apoptosis and proliferation. Cell migration and invasion were evaluated via transwell assay. The target association between molecules was confirmed by dual-luciferase reporter, RNA immunoprecipitation and RNA pull-down assays. Tumor xenograft assay was implemented to explore the role of circ_0085495 in vivo . Circ_0085495 and Integrin β1 were upregulated, while miR-873-5p was downregulated in ADM-resistant cells. Circ_0085495 was a stable circRNA, mainly located in the cytoplasm. Depletion of circ_0085495 repressed ADM resistance, proliferation and metastasis of ADM-resistant breast cancer cells, which was weakened by miR-873-5p inhibition or integrin β1 overexpression. Circ_0085495 sponged miR-873-5p to positively regulate integrin β1 expression. Integrin β1 knockdown also inhibited ADM resistance. Furthermore, circ_0085495 knockdown inhibited tumor growth in vivo . Circ_0085495 knockdown reduced ADM resistance in ADM-resistant cells through modulating miR-873-5p/integrin β1 axis, indicating circ_0085495 as a promising target for overcoming ADM resistance in breast cancer patients.